Early Postoperative Fasting Serum Glucose Levels are Useful in Depicting Future Diabetes Mellitus in Patients with Curative Insulinoma Surgery - Akca, Aycan; Starke, Achim A. R.; Dobek, Anna; Ulrich, Alexis; Goretzki, Peter E. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Hyperglycemia has been reported in some patients after curative insulinoma resection but no systematic investigation of glucose metabolism has been shown in a larger cohort of these patients. Therefore, it is still unknown, whether long lasting hyperinsulinism in insulinoma patients induces insulin resistance, which may jeopardize the postoperative health status of these patients.Methods Early postoperative fasting serum glucose levels were measured in all insulinoma patients after curative tumor resection during the first 48 h, being operated between 2011 and 2018, retrospectively.Results Of 77 (100%) patients with benign, spontaneous occuring insulinoma 51 (66.2%) patients were operated on by tumor enucleation. In 15 (19.5%) patients a left pancreatic resection was performed and in 11 (14.3%) patients the pancreatic head or the middle console of pancreatic corpus were excised. In 32 (41.6%) cases the highest fasting postoperative glucose levels were measured between 140–200 mg/dl. In 16 (20.8%) patients the glucose serum levels reached values above 200 mg/dl and in 4 (5.2%) patients short term substitution with insulin was indicated. Only one (1.3%) of these patients developed diabetes mellitus with the need of ongoing insulin treatment. Major postoperative complications were registered in 31 of all 77 patients (40.3%) and in 9 of 16 patients (56.3%) with postoperative glucose levels above 200 mg/dl. This difference was not statistically significant.Conclusions Early postoperative (first 48 h) fasting serum glucose levels in insulinoma patients showed significant hyperglycemia above 200 mg/dl in only few patients (20.8%) and chronic postoperative Diabetes mellitus developed in only one of 77 patients (<2%). Therefore, recovery of glucose metabolism after insulinoma resection is fast and medical intervention is not mandatory in most of these patients.
Keywords: insulinoma; hyperglycemia; postoperative; pancreas function; diabetes mellitus; insulin